Germany : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
The 2003 Article IV Consultation discussions took place against a backdrop of serious concerns about the health and prospects for the economy. The authorities saw the revised policy strategy as providing an important boost to confidence and the right balance of supply-side initiatives and demand-side support to revitalize growth. The key challenge in the financial sector is to maintain a healthy balance between competition and financial stability. The authorities have made progress in bringing key elements of their reform program closer to implementation.